Cicatrices : Central American fiction in the 21st century - Browitt, Jeff (Sussex Academic Press, 2020)
Cicatrices provides an understanding of the mood in Central American fiction over the last five years. Many recent novels and short stories are aesthetic responses to a difficult social, political and economic landscape dominated by neoliberal adjustment, drug trafficking, corruption and the struggle to establish fully democratic societies. Herein is a mix of male and female authors spread across five Central American countries: Guatemala, Nicaragua, El Salvador, Costa Rica and Honduras. Thematic unity is provided by nomadism, migration and the inability to leave behind a violent past of armed conflict that bleeds into the present--scars that won't heal. An atmosphere of survival, exhaustion, dissipation and decay (in both the physical and moral sense) dominates, but also rays of hope: the writers testify to the triumph of the spirit as much as to its destruction. This vibrant literature speaks of existential crisis in a context of social precarity and lack of opportunity as people dis-embedded by civil war and its aftermath seek release and fulfillment through migration across borders into neighbouring countries or north to the United States or Europe. Whether external or internal, self-imposed or forced, migration brings in train the problem of mal-adaptation to new worlds and struggles with memory & ndash; an aesthetics of loss and solitude. Various narrative strategies are adopted to try to account for this contemporary social reality, including crime fiction as critical realism, as well as auto-fiction